2013
DOI: 10.1007/s00467-013-2564-y
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from Prograf to Advagraf in stable paediatric renal transplant patients and 1-year follow-up

Abstract: Our results show that Advagraf bioequivalence cannot be ensured in this population. Significant changes in tacrolimus levels and dose were observed on long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 23 publications
5
24
0
Order By: Relevance
“…We found that renal function was stable in both kidney and liver transplant recipients after conversion from immediate‐ to prolonged‐release tacrolimus, in accordance with previous studies . Collectively, the efficacy data presented here suggest that conversion from immediate‐ to prolonged‐release tacrolimus is associated with a very low AR rate over 1 year in solid organ transplant recipients.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We found that renal function was stable in both kidney and liver transplant recipients after conversion from immediate‐ to prolonged‐release tacrolimus, in accordance with previous studies . Collectively, the efficacy data presented here suggest that conversion from immediate‐ to prolonged‐release tacrolimus is associated with a very low AR rate over 1 year in solid organ transplant recipients.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, only two (2.5%) kidney transplant recipients experienced AR, and there were no deaths or graft losses. These data are aligned with previous reports of pediatric kidney and liver transplant recipients converted from immediate‐ to prolonged‐release tacrolimus, in whom ARs were very low, or absent, over follow‐up periods ranging from 6 months to 5 years . For example, in a study of 11 pediatric stable kidney transplant recipients converted from immediate‐ to prolonged‐release tacrolimus, there were two BCAR episodes in one patient during the 1‐year follow‐up period .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations